2017
DOI: 10.1111/pbi.12667
|View full text |Cite
|
Sign up to set email alerts
|

H+‐pyrophosphatase IbVP1 promotes efficient iron use in sweet potato [Ipomoea batatas (L.) Lam.]

Abstract: SummaryIron (Fe) deficiency is one of the most common micronutrient deficiencies limiting crop production globally, especially in arid regions because of decreased availability of iron in alkaline soils. Sweet potato [Ipomoea batatas (L.) Lam.] grows well in arid regions and is tolerant to Fe deficiency. Here, we report that the transcription of type I H+‐pyrophosphatase (H+‐PPase) gene IbVP1 in sweet potato plants was strongly induced by Fe deficiency and auxin in hydroponics, improving Fe acquisition via inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 101 publications
(150 reference statements)
2
19
0
1
Order By: Relevance
“…served in the tissues of transformed basil roots ( In the present study, HA and SNP application significantly increased plasma membrane (PM) ATPase activity compared to the controls under both N- root primordia and cell differentiation [46]. In the present study, the application of HA and SNP increased the H + -PPase activity, in agreement with [5].…”
Section: Discussionsupporting
confidence: 83%
“…served in the tissues of transformed basil roots ( In the present study, HA and SNP application significantly increased plasma membrane (PM) ATPase activity compared to the controls under both N- root primordia and cell differentiation [46]. In the present study, the application of HA and SNP increased the H + -PPase activity, in agreement with [5].…”
Section: Discussionsupporting
confidence: 83%
“…Second, sugar signals originated from different sources, including active photosynthetic cells, dynamic storage reservoir, and organs for nutrient remobilization ( Li and Sheen, 2016 ). It has been identified that VHPs overexpression can promote soluble sugar accumulation in berry skin ( Figure 8E ), sweet potato leaves ( Fan et al, 2017 ) and apple callus ( Yao et al, 2011 ). The enhanced sugar concentration in vacuoles might elicit feedback signaling in the photosynthetic source to ensure the balance of carbon flow ( McCormic et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Third, SUT1 (also designated SUC1) plays a critical role in sucrose phloem loading and transport as well as cellular sugar partitioning ( Fan et al, 2017 ); loss of SUT1 function results in reduced sucrose transport, while increased SUT1 expression results in increased sucrose transport ( Kühn and Grof, 2010 ). The expression of SUT1 was up-regulated in the VvVHP1; 2 -overexpressing berry skins, IbVP1 -overexpressing sweet potato ( Fan et al, 2017 ) and AVP1 -overexpressing Arabidopsis ( Gaxiola et al, 2012 ). Therefore, VvVHP1; 2 might promote translocation of sucrose from source to sink tissues, at least partially, via up-regulation of VvSUT1 , and thereby induced modifications of sugar status.…”
Section: Discussionmentioning
confidence: 99%
“…TMCPVA could be divided into physical and chemical hydrogels . Generally, TMCPVA were obtained by a cross‐linking process of polymers, which might be achieved through a chemical reaction using high energy irradiation or through a physical reaction of polymer crystallization and/or hydrogen bonds. For chemically cross‐linking PVA hydrogels, glutaraldehyde as a traditional bifunctional cross‐linker could joint two PVA molecular chains so that the polymer network structure wasn't enough stable.…”
Section: Introductionmentioning
confidence: 99%